Mantle and fluid sources below Klyuchevskoy-Kamen-Bezymianny line (Kamchatka) - Churikova T.; Gordeychik B.; Wörner G. (Tokyo Institute of Technology, 2014)
Kamen volcano is an extinct volcanic complex located in the central part of the Klyuchevskaya group of volcanoes (KGV) between active Klyuchevskoy, Bezymianny, and Ploskie Sopky volcanoes. Kamen volcano was mapped by V.A. Ermakov only in the 1970s. However the modern geochemical studies of Kamen volcano have not been previously carried out and its relationship and petrogenesis in comparison to other active neighbors are unknown. A modern geochemical study of Kamen volcano is needed because it will shed light not only on the history of the volcano itself and its closest neighbors, but also on the history and magmatic evolution of the KGV melts in general. The distance between the summits of Kamen and Klyuchevskoy is only 5 km, the same as between Kamen and Bezymianny. The close relationship in space and time of the KGV and the common zone of seismicity below them suggests a common source and a possible genetic relationship between their magmas. However, the Late-Pleistocene-Holocene lavas of all these neighboring volcanoes are very different: high-Mg and high-Al Ol-Cpx-Pl basalts and basaltic andesites occur at Klyuchevskoy volcano, and Hbl-bearing andesites and dаcites dominate at Bezymianny volcano. The rocks of Ploskie Sopky volcano, situated only 10 km NW of Kamen, are represented by medium-high-K subalkaline lavas.